STUDI LITERATUR: PENGARUH KURANGNYA MOTIVASI SISWA TERHADAP PERILAKU HIDUP SEHAT(LITERATURE STUDY: THE INFLUENCE OF STUDENT'S LACK OF MOTIVATION ON HEALTHY LIVING BEHAVIOR) - Situmorang, Berri; Susanti, Revi; Arwita, Widya; Hasruddin, Hasruddin; Djulia, Ely; Askali, Nor-Aida (Jurnal Edukasi Biologi, 2025)
Motivation for healthy living is an effort to achieve optimal physical and mental health levels. One of the factors of healthy living behavior is the existence of healthy living motivation in a person. Students who have been equipped or have healthy living motivation will consistently carry out a healthy lifestyle. This condition is because the student is already motivated to maintain their health. However, if the student is not motivated to implement a healthy lifestyle, it will not be easy to maintain a healthy lifestyle consistently. The research method used in this study was an online search or literature study, which obtained information and data by analyzing valid research articles from both national and international sources. The study results showed that five articles examined the influence of motivation and healthy living behavior. Thus, motivation and healthy living behavior have a significant influence. As explained, the tendency to act is based on the motive to achieve a high degree of healthy living, and that person must have high motivation. The results of this study are expected to provide insight for other researchers to conduct similar research.